العلاقة بين استيعاب المفردات وتحصيل الطالبات التعليمي في مهارة الكلام للصف الأول من المتوسط بمعهد عبد الله بن مسعود أساهان - Sari, Maya; Karo, Tiy Kusmarabbi; Afandi, Ahmad (Lembaga Yasin AlSys, 2024)
Speaking skill is a productive skill that involves the process of learning various aspects of the Arabic language. To acquire this skill, one needs to understand grammar, morphology, vocabulary, style, and meanings. Proficiency in speaking Arabic requires comprehension of the elements and rules of the language, including vocabulary acquisition, sentence structure, speech context, and the ability to understand the speaker's language. Vocabulary is a very important linguistic element that must be mastered, used in both spoken and written language. This issue leads to weaknesses in vocabulary comprehension and the presence of excuses for not speaking Arabic in certain situations. The methodology used in this research is a quantitative correlational method, and the data analysis technique employed is the statistical method using Pearson's product-moment correlation coefficient. The research results indicate that there is a moderate positive correlation between vocabulary comprehension and students' academic achievement in speaking skills for the first-grade students at the Abdullah bin Masoud Institute in Asahan, with a correlation coefficient value of 0.474.